SCREENING OF FOXTAIL MILLET ( AIL MILLET (Setaria italica Setaria italica L.) GENOTYPES .) GENOTYPES AT DIFFERENT SOWING DATES FOR HIGHER RETURNS IN NORTHERN TRANSITION ZONE OF TELANGANA. - B. SRIKANYA; P.REVATHI; M. MALLA REDDY; K.CHANDRA SHAKER (The Bioscan, 2019)
A field experiment was conducted during Kharif season of 2017 at Regional Agricultural Research Station Polasa Jagatial, PJTSU to study the response of foxtail millet (Setaria italica L.) varieties to different dates of sowing. Among different varieties SIA 3085, recorded significant plant height ( 117.5cm), maximum number of tillers (m2) (93), number of ears / plant (5.10), grain yield (1350 kg ha- 1 ), stover yield (2559 kg ha-1 ) and harvest index (34.8 percent) as compared to other genotypes SIA 3156 and suryanandi. Among different dates of sowing crop sown on 30th August found significantly higher plant height (120.7 cm), maximum number of tillers (m2) (100), number of ears / plant (5.0), grain yield (1428 kg ha -1 ) , straw yield (2848 kg ha -1 ) and harvest index (33.5 %) as compared to 10th August, 20th August and 10th September dates of sowing. The maximum gross and net returns and B: C ratio was recorded in genotype SIA 3085 and crop sown on 30th August. The growth and yield of foxtail millet genotype SIA 3085 and sowing date 30th August provides favourable weather condition for better growth, yield and profitable under Transition Zone of Telangana condition.